Cross-border cooperation of enterprises: essence and significance - Kuzmin, O.; Kravchenko, I. (Commission of Motorization and Energetics in Agriculture, 2014)
In the last decade the development of cross-border cooperation in the context of economic integration and internationalization processes becoming increasingly important for Ukraine, which follows the Western vector of integration. Systematic development of cross-border cooperation is not possible without considering all of its components and levels. The article highlights a vision of complicated economic phenomenon – the cross-border cooperation of enterprises, which combines the two important economic categories – cross-border cooperation and entrepreneurship by its self. There considered the fact that cross-border cooperation is an important tool for economic development and competitiveness increase of enterprises, located in border areas.
Keywords: cross-border cooperation (CBC); international entrepreneurship; foreign economic activity (FEA) of enterprises; cross-border cooperation of enterprises